The effect of empowerment on performance through commitment and creativity as a mediation variable in Maritime Sector MSMEs in Sumenep Regency - Alvin Arifin; Rachmad Hidayat (Technium Social Sciences Journal, 2023)
This study used commitment and creativity as mediating factors to examine the effects of empowerment on performance. The Micro small and Medium Enterprises (MSMEs) Maritime Sector in Sumenep Regency is the subject of this study’s attention. Due to their importance to the community’s economy, MSMEs must perform well. This study utilized a saturated sample, or all 57 respondents, from a population of 57 MSME players. The method of gathering data involves giving out questionnaires to participants, who then return them all in full, ensuring that no questionnaires are left unfilled. SEM-PLS, or structural equation modeling, was employed for data analysis. The findings of this study show that empowerment has a positive and not significant impact on organizational commitment, empowerment has a positive and significant impact on performance, empowerment has a positive and significant impact on creativity, commitment has a positive and not significant impact on performance, and commitment does not act as a mediator between empowerment and performance or creativity. This study is anticipated to serve as a foundation for decisions about the district of Sumenep’s MSMEs.